Effect of dietary blend of canola oil and palm oil on fatty acid composition, color and antioxidant profile of Biceps femoris muscle in goats - Adeyemi, Kazeem Dauda; Sazili, Awis Qurni; Sabow, Azad Behnan; Karim, Roselina; Ismail, M. (2015)
This study examined the effect of blend of 80% canola oil and 20% palm oil (BCPO) on lipid composition, antioxidant status, color and oxidative stability of Biceps femoris (BF) muscle in goats. Twenty-four bucks were randomly assigned to diets containing 0, 4 or 8% BCPO, fed for 14 weeks and slaughtered. Diet had no effect on glutathione peroxidase, catalase and superoxide dismutase activities. Goats fed 4% BCPO had higher (P<0.05) CLA cis-9 trans-11 while 8% BCPO had higher C18:3n-3 compared to other treatments. The 4 and 8% BCPO meat had lower (P<0.05) C14:0 and C15:0 and higher C22:5n-3 than did control goats. Dietary BCPO improved α and γ-tocopherol, redness and oxidative stability but did not affect total carotenoids and δ-tocopherol. Dietary BCPO enhanced beneficial muscle lipids without compromising color and lipid stability.